Qualidade subjetiva do sono e queixa de insônia em pacientes com Acidente Vascular Cerebral - Rocha, Patrícia Cavalcanti da (2008)
Brain injury can be associated with changes in the sleep-wake cycle. However, studies about sleep disturbances and their relationship with quality of sleep are scarce. Besides, it remains to be known how stroke affects the mechanisms of sleep. The aim of this study was to investigate quality of sleep, complaints of sleep disturbances and associated factors in stroke patients from the Physical Therapy services in Natal -RN. This was a cross-sectional descriptive study involving 70 individuals (aged 45-65 years), 40 patients (57 ± 7 years), 11 ± 9 months after injury, and 30 healthy individua ls (52 ± 6 years), evaluated with the Pittsburgh Sleep Quality Index (PSQI) and Sleep Habits Questionnaire. The data were analyzed by Chi-square test, t Student test and logistic regression. Poor quality sleep was found in 57,5% of the patients (6,3 ± 3,5) and was significantly higher than in the control population (3,9 ± 2,2) (t Student test, p=0,002). The patients showed significantly higher value of PSQI than controls: sleep latency (p=0,019), length of sleep (p=0,039) and dysfunction during the day (p=0,001). Regarding complaints of sleep disturbances (dyssomnias and parasomnias) analyzed by Chi-square test, the complaint of insomnia was the most prevalent (patients: 37,5%; healthy subjects: 6,7%; p=0,007). Regression analysis showed that sl eep latency (p=0,036) and complaint of insomnia (p=0,036) were associated with quality sleep. In addition, female gender (p=0,036) and complaint of broken sleep (p=0,003) were considered risk factors for the presence of insomnia. Our results show that stroke affects the homeostatic process of sleep. Shorter sleep latency and the absence of insomnia are considered protective factors for good sleep quality and this should be taken into consideration in the diagnostic and therapeutic strategies